2016
DOI: 10.1088/2040-8978/18/6/065004
|View full text |Cite
|
Sign up to set email alerts
|

Extremely narrow resonances, giant sensitivity and field enhancement in low-loss waveguide sensors

Abstract: Low-loss waveguides (WGs), which support excitation of waveguide modes (WMs), are based on a dielectric WG separated from an absorptive film by a low-index dielectric spacer layer. We perform numerical and analytical study of the impact of the losses imposed to the WG in a planar sensing structure in the Kretschmann configuration on the resonance properties of the excitation. We demonstrate that the loss degree of the WMs can be controlled by the thickness of the spacer layer for both s and p polarizations. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 45 publications
1
36
0
1
Order By: Relevance
“…It has been reported that a layered waveguide structure can generate a stronger and thicker enhanced electric field101112. Therefore, a sensor chip with a 36-nm thick Si layer and 364-nm thick SiO 2 layer placed on a 0.725-mm thick SiO 2 substrate was employed in the present system.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that a layered waveguide structure can generate a stronger and thicker enhanced electric field101112. Therefore, a sensor chip with a 36-nm thick Si layer and 364-nm thick SiO 2 layer placed on a 0.725-mm thick SiO 2 substrate was employed in the present system.…”
Section: Resultsmentioning
confidence: 99%
“…This Another metric that affects the sensor performance is the sensitivity by intensity. This metric relates the change in the power level to the change of the refractive index and is given by equation (7) as defined in [39][40][41]. For the proposed sensor, the maximum value for sensitivity by intensity is around 300 RIU −1 which is two orders of magnitude smaller when compared to 3.2 × 10 4 RIU −1 reported in [39] and 1.4 × 10 7 RIU −1 reported in [41].…”
Section: Optimized Gas Sensormentioning
confidence: 95%
“…This metric relates the change in the power level to the change of the refractive index and is given by equation (7) as defined in [39][40][41]. For the proposed sensor, the maximum value for sensitivity by intensity is around 300 RIU −1 which is two orders of magnitude smaller when compared to 3.2 × 10 4 RIU −1 reported in [39] and 1.4 × 10 7 RIU −1 reported in [41]. On the other hand, for the proposed sensor in this paper, an angular sensitivity of 120°RIU −1 is maintained compared to 30°RIU −1 reported in [39] and 16°RIU −1 reported in [41], which is four times greater than that reported in [39,41].…”
Section: Optimized Gas Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…Известно, что поверхностные волны могут распространяться и в диэлектрических [17], и комбинированных металлодиэлектрических [18] пленках планарных волноводов. В связи с этим было предложено [12,19] по схеме Кречмана возбуждать поверхностную волну в многослойной чисто диэлектрической структуре, представляющий из себя планарный волновод.…”
Section: введение и постановка задачиunclassified